PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MODEL PROJECT BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIK - Noviana Kusumawati (LPPM Universitas Pekalongan, 2012)
The objectives of this research is: (1) generate the PBL learning model in the linear program material to enhance the communication skill of Mathematical valid, (2) obtain the effectiveness of learning mathematics model PBL. Activity of independent variables while the dependent variable mathematics communication skill. The results: (1) equipments developed valid, (2) learning process using PBL effective, marked the achievement of: a) the exhaustiveness indivudually mathematics communication skill test exceed for KKM and classical completeness exceed 70%, b) activity has a positive effect on the mathematics communication skill, c) average of mathematics communication skill test experiment class is better than the control class. Based on the validation result obtained are valid and effective learning, then the purpose of learning instrument development is achieved. Therefore, to improve the communication skill of students in the linear program materials and other materials with the same characteristics suggested PBL model that has been developed so that the media to improve communication skill math students more varied.Keywords: Project, Communication.